(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
The development of digital technology brings significant changes to social life and education, while also presenting challenges to the character formation of the younger generation. This study aims to analyze the role of Islamic morals (akhlaq) in shaping national character in the digital era. The method used is a literature review with a qualitative approach, examining books, journals, and recent scientific sources related to Islamic character education, akhlaq, and the use of digital technology in education. The results show that Islamic morals, including values such as honesty, responsibility, empathy, and manners, serve as a moral foundation that guides individual behavior in both online and offline interactions. The integration of akhlaq in formal education, family habituation, and the use of interactive digital media creates a conducive environment for the internalization of moral values. Character education based on Islamic morals has proven to develop a generation that is not only intellectually competent but also morally and spiritually resilient. Collaboration among schools, parents, communities, and religious institutions is a key factor in successful value internalization. This study confirms that Islamic morals can serve as a pillar in shaping a national character that is adaptive and has integrity, providing a foundation for educational strategies that align with technological development.